P﻿orous rubber materials with temperature-responsive property - Zeshang Jiang; Jiacheng Yu; Wuchao Cheng; Zhenxiang Xin; Jieting Geng; Lin Xia (eXPRESS Polymer Letters)
Inspired by the micro structure of loofah sponge in nature, this article successfully employs a biomimetic approach to develop a novel series of natural Eucommia rubber foamed materials with excellent shape memory properties. This article explores the characteristic features of natural Eucommia ulmoides rubber foamed materials, including the foaming process, mechanical properties, shape memory performance, and adsorption properties. This paper introduces the innovative use of natural Eucommia ulmoides rubber’s shape memory properties to create a temperature-responsive foam adsorbent material. The foamed material’s unique ability to modify its pore structure through simple compression and heating processes offers tailored adsorption speed and capacity for varied practical applications. The adjustable adsorption properties of this foamed material present novel opportunities for its utilization in adsorption applications.